Рим первых царей: Генезис рим. полиса / И. Л. Маяк - Маяк Ия Леонидовна (издательство МГУ, 1983)
Экземпляры: ЧЗ (20181002) / Инвентарный номер: 5750 / Цена: 1.70 / Сис.шифр: 63.3(0)323 / Авт.знак: М 39 / ГРНТИ: 03 / ББК: 63.3(0)323